Genetic variation in the complex Acanthosaura coronata species group and record of sexual dimorphism - Hai, Ngo Ngoc; Le, Tu Hoang Linh; Nguyen, Thien Tao; Nguyen, Thi Nhu Quynh; Nguyen, Hoang Van; Nguyen, Thi Truc Thanh (Vietnam Journal of Biotechnology, 2026)
The two recently described species, Acanthosaura cuongi and A. grismeri in southern Vietnam, highlight the potential existence of additional populations or even undescribed species in this region, rather than supporting the previous assumption that Acanthosaura coronata is broadly distributed across southern Vietnam. Phylogenetic analysis of COI gene sequences confirmed the monophyly of the A. coronata group, comprising A. coronata, A. cuongi, and A. grismeri. In southern Vietnam, two new populations from Gia Lai Province were assigned to A. cuongi, while one new population from Tay Ninh Province was identified as A. coronata. Within the group, interspecific p-distances ranged from 7.82–8.77% between A. coronata and A. grismeri, to 13.5–14.92% between A. coronata and A. cuongi, and 13.84–15.19% between A. cuongi and A. grismeri. Intraspecific genetic divergences were up to 3.22% in A. cuongi and 2.66% in A. coronata, suggesting potential cryptic diversity and emphasizing the need for further taxonomic assessment using additional molecular data. Based on morphological data from 66 individuals, this study provided a comprehensive redescription of A. coronata species and documented distinct sexual dimorphism. Males exhibit light green to yellow-green dorsal coloration and an orange-red tail likely functioning in sexual signaling, whereas females display dull brown-gray coloration enhancing camouflage. Morphometric analyses revealed female-biased traits, including greater snout–vent length and abdominal width, potentially improving fecundity and egg survival. Conversely, males possess longer heads, limbs, and broader tail bases, which may facilitate greater agility and provide advantages in hunting, territorial defense, and reproductive success. These findings contribute to a better understanding of morphological variation, sexual dimorphism, and taxonomic relationships within the complex A. coronata group.